Prevalence of Autism Spectrum Disorder among Rural, Urban, and Tribal Children (1–10 Years of Age) - Raina, Sunil Kumar (J Neurosci Rural Pract, 2017)
INTRODUCTION: Studies on autism spectrum disorders (ASDs) have largely focused on children in specific settings. The current scenario of research in ASDs is limited largely to clinic-based case reports, case series, and retrospective chart reviews. The present study is the first population-based prevalence study conducted across rural, urban, and tribal populations in India. MATERIALS AND METHODS: A cross-sectional two-phase study was conducted covering children in the age group of 1–10 years of age across geographical regions representing rural, urban, and tribal populations. The first phase (screening phase) involved administration of the Hindi version of the Indian Scale for Assessment of Autism. Those identified as suspected of ASD and 10% of all classified as nonsuspects for autism were also evaluated by the clinical team in second phase (evaluation phase). RESULTS: Forty-three children out of a total of 28,070 children in rural, urban, and tribal area in the age group of 1–10 years were diagnosed as cases of ASD yielding a prevalence of 0.15% (95% confidence interval [CI] =0.15–0.25). Logistic regression analysis showed a two times significantly higher risk of diagnosing ASD in rural area as compared to tribal (odds ratio [OR]; 95% CI = 2.17 [1.04–4.52], P = 0.04). Male sex and upper socioeconomic group of head of family/father had a higher risk of getting diagnosed as autism as compared to lower socioeconomic group (OR; 95% CI - 3.23; 0.24–44.28, P = 0.38). CONCLUSIONS: Estimation of true prevalence of ASD in India is going to improve policies on developmental disabilities.